The neuromuscular and multisystem features of RYR1-related malignant hyperthermia and rhabdomyolysis: A study protocol. Issue 33 (20th August 2021) - van den Bersselaar, Luuk R.; Kruijt, Nick; Scheffer, Gert-Jan; van Eijk, Lucas; Malagon, Ignacio; Buckens, Stan; Custers, José AE; Helder, Leonie; Greco, Anna; Joosten, Leo AB; van Engelen, Baziel GM; van Alfen, Nens; et al.
Abstract: Introduction: Malignant hyperthermia (MH) and exertional rhabdomyolysis (ERM) have long been considered episodic phenotypes occurring in response to external triggers in otherwise healthy individuals with variants in RYR1 . However, recent studies have demonstrated a clinical and histopathological continuum between patients with RYR1 -related congenital myopathies and those with ERM or MH susceptibility. Furthermore, animal studies have shown non-neuromuscular features such as a mild bleeding disorder and an immunological gain-of-function associated with MH/ERM related RYR1 variants raising important questions for further research. Awareness of the neuromuscular disease spectrum and potential multisystem involvement in RYR1 -related MH and ERM is essential to optimize the diagnostic work-up, improve counselling and and future treatment strategies for patients affected by these conditions. This study will examine in detail the nature and severity of continuous disease manifestations and their effect on daily life in patients with RYR1 -related MH and ERM. Methods: The study protocol consists of four parts; an online questionnaire study, a clinical observational study, muscle imaging, and specific immunological studies. Patients with RYR1 -related MH susceptibility and ERM will be included. The imaging, immunological and clinical studies will have a cross-sectional design, while the questionnaire study will be performed three times during a year to assess disease impact, daily living activities, fatigue and pain. The imaging study consists of muscle ultrasound and whole-body magnetic resonance imaging studies. For the immunological studies, peripheral mononuclear blood cells will be isolated for in vitro stimulation with toll-like receptor ligands, to examine the role of the immune system in the pathophysiology of RYR1 -related MH and ERM. Discussion: This study will increase knowledge of the full spectrum of neuromuscular and multisystem features of RYR1 -related MH and ERM and will establish a well-characterized baseline cohort for future studies on RYR1 -related disorders. The results of this study are expected to improve recognition of RYR1 -related symptoms, counselling and a more personalized approach to patients affected by these conditions. Furthermore, results will create new insights in the role of the immune system in the pathophysiology of MH and ERM. Trial registration: This study was pre-registered at ClinicalTrials.gov (ID: NCT04610619).